THE EFFECT OF READING ALOUD ON THE UTTERANCES OF EARLY SET OF WORDS IN THE REHABILITATION OF A HEARING-IMPAIRED BOY WITH COCHLEAR IMPLANT A CASE STUDY - Suzanne, Suzanne (Universiti Malaysia Sarawak, UNIMAS, 2005)
This study sought to find out the effects of reading aloud on the utterances of e arly s et of w ords in the re habilitation of a hearing - impaired boy with cochlear implant. The subject in the study is a hearing impaired boy who h ears with a sensory hearing aid . C ochlear implantation was done one and half years ago. T he study uses the reading aloud treatment (R.A.T) to provide spoken language to the subject. The reading materials contain four categories of words, namely, naming things and people; actions and events; describing or modifying things and personal or socia l words. In the process of the re habilitation, the reading materials were read to the subject. Then the subject read aloud by repeating what is been read. It is one of the strategies that can be used to support language development in all children. T he findings show that there is a great increase in the number of words uttered and imitated by the subject. The words were from the nominal category of words where the types of words were generally nouns. T he subject was able to develop further to use th e words in the correct contexts.